Attending sporting mega events during COVID-19: mitigation and messaging at UK EURO 2020 matches. (7th January 2023) - Purves, Richard I; Maclean, Jordan; Rocha, Claudio; Philpott, Matthew; Fitzgerald, Niamh; Piggin, Joe; Hunt, Kate
Summary: The UEFA EURO 2020 football tournament was one of the largest Sporting Mega Events (SMEs) to take place during the COVID-19 pandemic. Mitigating the risk of virus transmission requires a multi-layered approach for any large event, more so in this case due to staging the tournament across eleven host countries. Yet, little is known about COVID-19 risks and mitigation from attending an event of this scale and nature. We examined the implementation of mitigation and messaging at EURO 2020 matches hosted at venues in the UK. The tournament was postponed from the summer of 2020 and played in June and July of 2021. Structured observations were conducted by 11 trained fieldwork-supporters at 10 matches played at Wembley Stadium, London, or Hampden Park, Glasgow. Fieldwork-supporters observed one-way systems and signage, and hand sanitizing stations inside the stadia, but reported significant variation in the implementation of staggered timeslots, testing upon entry, and procedures for exit. Adherence to planned measures by ticket holders and implementation by stewards waned as the tournament progressed culminating in an absence of enforced measures at the final. The non-compliance with COVID-19 mitigation measures was likely to have led to a significantly increased risk of transmission. Future events should consider how COVID-19 mitigation measures could become 'new norms' of fan behaviour, learning from what is already known about football fandom. Tournament organizers of SMEs can use these findings to promote clearer messaging on pandemic-driven changes in fan behaviour and best practices in mitigating risk at future sporting and cultural events. Lay Summary: The UEFA EURO 2020 football tournament saw one of the largest returns to spectating at sporting events during the COVID-19 pandemic. With the tournament taking place across 11 different countries, several measures (e.g. mask-wearing and social distancing) were put in place to protect ticket holders from spreading and catching COVID-19, and these were communicated to spectators before and during matches. This study considers how these measures were implemented at EURO 2020 matches hosted in the UK. Despite retaining the name 'EURO 2020', the tournament was postponed from the summer of 2020 and played in June and July of 2021. We recruited and trained 11 ticket holders who became observers at 10 matches played at Wembley Stadium, London, or Hampden Park, Glasgow. The results demonstrate that supporting normally at football matches during the pandemic times increased the risk of virus transmission. There were inconsistencies in how mitigation measures were planned and implemented by tournament organizers. Ticket holders were also less compliant with mitigation measures as the tournament progressed, likely made more difficult with relaxations in government restrictions. To limit virus transmission at future sporting and cultural events, messaging on mitigation measures must be clear, consistent and implemented as planned.